2015
DOI: 10.1007/s10681-015-1373-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability for root and shoot traits in a lentil (Lens culinaris Medik.) recombinant inbred line population and their association with drought tolerance

Abstract: Lentil (Lens culinaris Medik.) is usually grown under rainfed environments and often encounters drought stress from limited rainfall. Little information is available about shoot and root traits in association with drought tolerance. We studied variability for root and shoot traits related to drought tolerance using an F6–8 population of 133 recombinant inbred lines (RILs) from the cross ILL6002 × ILL5888. We found important variation between genotypes and also high variation in heritability values for root and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 38 publications
3
34
0
6
Order By: Relevance
“…Similar root and shoot traits variability related to drought tolerance in lentil was also observed by Idrissi et al . where they found that drought stress significantly reduced root and shoot characteristics compared to well-watered conditions in RILs derived from a cross between ILL 6002 and ILL 5888 [ 33 ]. Ashraf and Iram also found that imposition of water deficit conditions on Phaseolus vulgaris and Sesbania aculeata plants had significant inhibitory effect on fresh and dry weights of both root and shoot as well as on shoot length [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar root and shoot traits variability related to drought tolerance in lentil was also observed by Idrissi et al . where they found that drought stress significantly reduced root and shoot characteristics compared to well-watered conditions in RILs derived from a cross between ILL 6002 and ILL 5888 [ 33 ]. Ashraf and Iram also found that imposition of water deficit conditions on Phaseolus vulgaris and Sesbania aculeata plants had significant inhibitory effect on fresh and dry weights of both root and shoot as well as on shoot length [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…and Idrissi et al . [ 16 , 33 ]: 0 = healthy plants with no visible symptoms of drought stress; 1 = green plants with slight wilting; 2 = leaves turning yellowish green with moderate wilting; 3 = leaves yellow—brown with severe wilting and 4 = completely dried leaves and/or stems. The reduction of root length and shoot length, fresh and dry weights was also recorded after 6 days of air exposure at the seedling stage.…”
Section: Methodsmentioning
confidence: 99%
“…These traits were shown to be significantly correlated (Idrissi et al, 2015a). Similarly, a QTL-“hotspot” related to 12 root traits was reported by Varshney et al (2014) in chickpea ( Cicer arietinum L.).…”
Section: Discussionmentioning
confidence: 99%
“…Idrissi et al (2015a) confirmed evidence of high genetic variability, high heritability and polygenic control of root and shoot characteristics. However, to our knowledge, no QTLs related to root traits have been reported for lentil to date.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation